Study Of Mixed Reality Technologies In Presenting A Malaysian Herbs For Learning - Jamal, Jazmi Izwan (2011)
The purpose of this paper is to study the mixed reality technologies to be implemented for herb-related subject particularly in pharmacognosy course. A study is conducted by identifying mixed reality learning affordance in helping the learners to enhance learning about herb\'s physical characteristic, examining existing displays, tracking techniques, and multimedia elements for mixed reality technologies and determining the types of mixed reality technologies that are suitable to present herb for learning.